A nurse‐guided, basal‐prandial insulin treatment protocol for achieving glycaemic control of hospitalized, non‐critically ill diabetes patients, is non‐inferior to physician‐guided therapy: A pivotal, nurse‐empowerment study. Issue 6 (1st April 2014) - Segal, Gad; Karniel, Eli; Mahagna, Ahmed; Kaa'dan, Fadi; Levi, Zehava; Balik, Chaya
Abstract : Basal‐prandial insulin is established for glycaemic control for hospitalized, type 2 diabetes patients. Empowering nurses to guide such protocols could be advantageous.The study aims to comparatively assess the efficacy and safety of glycaemic control by a nurse‐guided protocol with physician‐guided therapy. It also aims to assess the impact of empowerment on the nurses' sense of competence. This is a prospective, controlled, randomized, single‐blinded study. Validated protocol utilizing basal‐prandial insulin was used. Glycaemic control was the primary efficacy outcome, whereas hypoglycaemia and laboratory parameters were followed for safety. Assessment of nurses' psychological empowerment was done. One hundred fifty‐eight treatment days of 53 patients were included. Patients were randomized to either study group ( n  = 27) or control group ( n  = 26). Glycaemia deviation from liberal range (60–300 mg/dL) was 7.4% of days for nurse‐guided, basal‐prandial insulin treatment protocol (NGP) and 7.84% for physician‐guided therapy (PGT), P  = 0.901. Rate of glycaemia deviation from the strict range (100–180 mg/dL) was 49.76% for NGP and 47.38% for PGT, P  = 0.703. Mean range of daily deviation was similar (77.05 mg/dL for NGP and 76.04 mg/dL for PGT, P  = 0.93). There were no significant differences in safety parameters. An empowerment questionnaire showed tendency for increased nurses' sense of competence. Nurse‐guided protocol is non‐inferior to physician‐guided treatment in efficacy and safety parameters. Nurses' sense of competence was positively influenced.